Towards relational sociology - Crossley, Nick, 1968- (International library of sociology., 2011)
Argues that social worlds comprise networks of interaction and relations. This book demonstrates how networks comprise multiple dyadic relations which are mutually transformed through their combination. It covers many of the key concepts and concerns of contemporary sociology, including identity, power, exchange and meaning.